Pengembangan Dan Implementasi Moodle Untuk Mobile Learning Berbasis Android (Studi Kasus : SMK KRISTEN GERGAJI SEMARANG) (Information Technology and Telematics, 2015)
Abstract The technological sophisticationis growing rapidlymakes the function of Smartphones evolve not only become aregular communication tool.The use of Smartphonesare expected to help Christian Vocational School Students Gergaji Semarang in teaching and learning process throughe-learning systembased on Android. This application made with Java, XML, and PHP progamming and also CMS Moodle for the e-learning. Smartphones which used in this application are 2.2 Version (Froyo) or above. E-learning system based on Android, advantageous for teaching a    nd learning process. The students may look the materials, dowloading and uploading the materials and tasks with this application, they also may look the their scores given by their teacher through Android Smartphone. Keywords: Android, E-Learning, Smartphone